Analysis of Chemical Compound Content and Magnetic Properties of Iron Sand in Rondo Woing Village, East Manggarai - Yudhawardana, Hartoyo; F. Lalus, Heri (Department of Physics Education, Universitas Mataram, 2023)
The mine sand extraction process used the Methanol Soap Bathed (MSB) method. The results of sample analysis using XRF and VSM (Vibrating Sample Magnetometer) obtained that the most dominant compound content was Silica (SiO2), Iron (Fe2O3), Quicklime (CaO), and Alumina (Al2O3). At the same time, the sample results from the Vibrating Sample Magnetometer (VSM) show that Rondo Woing East Manggarai iron sand has soft magnetic properties. The iron sand sample with code 001 has Hc, Mr, and Ms of 324.83 Oe, 0.31 emu/gram, and 1.61 emu/gram, respectively. The iron sand sample with code 002 has Hc, Mr, and Ms of 319.91 Oe, 0.31 emu/gram, and 1.6 emu/gram, respectively. The results of the analysis show that four dominant elements are the same; namely, Fe is the most dominant element in Fe2O3 compounds, with 32.3%, Al elements in Al2O3 compounds, with levels of 13%, Si in SiO2 compounds with levels of 31.1% and Ca in a CaO compound with a content of 17.7% and Ti in a TiO2 compound of around 2%, so that the iron sand at Rondo Woing shows magnetic material properties.